2017
DOI: 10.1097/meg.0000000000000871
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and tolerability of direct-acting antivirals in elderly patients with chronic hepatitis C

Abstract: BackgroundThere is a lack of evidence-based data on aged patients with newer direct-acting antivirals (DAAs) and with shorter duration of treatment regimens involving DAAs with or without ribavirin (RBV) and pegylated interferon (Peg IFN).Patients and methodsMedical records of 240 patients treated with DAAs with or without Peg IFN and RBV between January 2013 and July 2015 were retrospectively analyzed. Patients were divided into two groups: patients aged 65 years and older (N=84) and patients aged younger tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Seven studies reported data on the prevalence of skin complaints in different age subgroups and reported a slight increase in the frequency of pruritus, rash and photosensitivity in patients aged ≥ 65 years (7% vs 9.9%; OR 0.61 95%CI: 0.45‐0.83; P = 0.001) . To verify the impact of protease inhibitors in the prevalence of skin complaints in older adults, a subgroup analysis only including patients without protease inhibitors in the antiviral regimen was performed and we did not observe any significant difference (OR 0.62 95%CI: 0.31‐1.26; P = 0.19).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Seven studies reported data on the prevalence of skin complaints in different age subgroups and reported a slight increase in the frequency of pruritus, rash and photosensitivity in patients aged ≥ 65 years (7% vs 9.9%; OR 0.61 95%CI: 0.45‐0.83; P = 0.001) . To verify the impact of protease inhibitors in the prevalence of skin complaints in older adults, a subgroup analysis only including patients without protease inhibitors in the antiviral regimen was performed and we did not observe any significant difference (OR 0.62 95%CI: 0.31‐1.26; P = 0.19).…”
Section: Resultsmentioning
confidence: 73%
“…Safety outcomes were reported by 10 studies (1 RCT, 1 SAT and 8 observational studies) . The risk of bias of the included studies is shown in Table and .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of HCV has shifted toward more tolerable, safer oral regimens with the use of direct-acting antiviral agents (DAAs). These regimens have truly revolutionized the efficiency of HCV treatment by achieving a sustained virologic response (SVR), shortening the duration of treatment, and improving patient outcomes without the burden of neuropsychiatric adverse effects [11,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%